Application of Traditional Chinese Medicine nursing combined with humanistic nursing intervention in elderly patients with insomnia (中医特色护理联合人文关怀在老年失眠患者中的应用效果观察) - TIAN Zheng (田征); YE Yun (叶云); LI Qianqian (李倩倩) (Journal of International Translational Medicine Limited, 2024)
Objective To observe the effect of Traditional Chinese Medicine nursing technique combined with humanistic nursing intervention in the treatment of elderly patients with insomnia. Methods Totally 80 elderly patients with insomnia were divided into observation group and control group, 40 cases in each group. The control group was given routine nursing, and the observation group was given TCM techniques-auricular acupoint pressing combined with humanistic nursing intervention. The sleep quality was evaluated by Pittsburgh Sleep quality index (PSQI)before and after 2 months of intervention. Results The PSQI score was decreased in both two groups after intervention, and PSQI score in the observation group was lower than that in the control group, with a significant difference(P＜0. 01). Conclusion TCM nursing technique combined with humanistic nursing intervention can effectively improve sleep quality of elderly patients with insomnia (目的 探讨中医特色护理技术联合人文关怀护理干预老年失眠患者的效果观察。方法 选取2019年5月-2020年5月医院收治的80例老年失眠患者为研究对象, 分为观察组与对照组, 各40例。对照组给予常规护理, 观察组在对照组基础上给予中医耳穴贴压联合人文关怀护理。采用匹兹堡睡眠质量指数(PSQI)评估患者干预前及干预2个月后睡眠功能改善情况。结果 干预后, 两组PSQI量表评分均较干预前降低, 且观察组PSQI评分低于观察组, 差异有统计学意义(P＜0. 01)。结论 中医特色护理技术耳穴贴压联合人文关怀护理干预能有效改善老年失眠患者睡眠质量。)